Beneficial effects of vitamins D and K on the elastic properties of the vessel wall in postmenopausal women: a follow-up study - Braam, Lavienja A. J. L. M.; Hoeks, Arnold P. G.; Brouns, Fred; Hamulyák, Karly; Gerichhausen, Monique J.W.; Vermeer, Cees (Thrombosis and Haemostasis, 2004)
Matrix-Gla Protein (MGP) is a strong inhibitor of vascular calcification, the expression of which is vitamin D dependent. MGP contains five γ-carboxyglutamic acid (Gla)-residues which are formed in a vitamin K-dependent carboxylation step and which are essential for its function. Hence vascular vitamin K-deficiency will result in undercarboxylated, inactive MGP which is a potential risk factor for calcification. In the present study we describe the effects of vitamin K1 and D supplementation on vascular properties in postmenopausal women. In a randomized placebo-controlled intervention study, 181 postmenopausal women were given either a placebo or a supplement containing minerals and vitamin D (MD-group), or the same supplement with vitamin K1 (MDK-group). 150 participants completed the study and analysis was performed on 108 participants. At baseline and after three years, vessel wall characteristics, including compliance coefficient (CC), distensibility coefficient (DC), intima-media thickness (IMT) and the Young’s Modulus (E) were measured to assess the effect of the supplements on the change of these parameters. The results showed that the elastic properties of the common carotid artery in the MDK-group remained unchanged over the three-year period, but decreased in the MDand placebo-group. Comparing the MDKand placebo-group, there were significant differences in decrease of DC (8.8%; p<0.05), CC (8.6%; p<0.05), and in increase of PP (6.3%; p<0.05) and E (13.2%, p<0.01).There were no significant differences between the MD-group and placebo. No significant differences were observed in the change of IMT between the three groups. It is concluded that a supplement containing vitamins K1 and D has a beneficial effect on the elastic properties of the arterial vessel wall.
Keywords: Elastic properties; vessel wall; vitamin K; postmenopausal women; ultrasound